Reviews Film. Issue 3 (1st September 2014) - Cziborr, Jonathan; Fleischmann, Dustin; Incrucio, Mars; Jonathan King, Justin Ray
Like Father, Like SonLike Father, Like Son (Soshite chichi ni naru, 2013)Japan Director Hirokazu Koreeda Runtime 120 minutesAn Achievement in Storytelling: A Review of Spike Jonze's HerHer (2013) USA Director Spike Jonze Runtime 126 minutesOnly Refn ForgivesOnly God Forgives (2013) Denmark/Sweden/ Thailand/USA/France Director Nicolas Winding Refn Runtime 90 minutesMan of SteelMan of Steel (2013) USA/Canada/UK Director Zack Snyder Runtime 143 minutes